Redesign the Best Model for Lower Link Arm in the MF Tractor by Finite Element Analysis - Tariq Mahmoud Chliab; Ali Adelkhani (Journal of Techniques)
The lower link arm of the tractor is one of the parts that are exposed to heavy static, dynamic, and fatigue loads. If the lower link arm is damaged, the agricultural operations will be stopped and the machinery connected to it will also be damaged. Therefore, it is necessary to design this arm so that it is resistant to various loads. This article redesigns and analyzes the MF Extra 290 tractor's lower link arm in response to plowing power. SolidWorks software was used to design different arm models, and stress was analyzed using Abaqus software. Nine different arm models were designed with three different cross-sectional shapes (Rectangular-Narrow Center) and three volume methods (Straight, Vertical Convex, and Horizontal Convex). The best arm model, according to the results, is an extruded one with a rectangle-shaped, wide center. The safety factor for this model of the arm is 1.82. In all arm models, maximum stress was observed in the hole connecting the lower arm to the hydraulic jack of the tractor.